1995
DOI: 10.1203/00006450-199509000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxic Injury of Immature Guinea Pig Lung Is Mediated via Hydroxyl Radicals

Abstract: Curdiovnsculal-Re,rearch, T h R a y n~Suppnrt of preterm infants with ventilation and oxygen therapy frequently leads to Lhe development of chronic lung disease. Oxidative stress, rhmugh the generation of excess oxygen free radicals, is thought to play a major role in this condition. At present the radical species responsible for oxidative lung ~n j u r y is not known, and cKcctive antioxidant based therapies are not available. The purposc of this study was to determine whether hydroxyl rad~cals, potent reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 19 publications
0
19
0
2
Order By: Relevance
“…The determination of otyrosine was carried out after acid hydrolysis of liver samples by an HPLC method given in a previous paper (31,32). Briefly, The hydrolysates were evaporated to dryness on a Pierce Reactitherme at 60°C and redissolved in distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…The determination of otyrosine was carried out after acid hydrolysis of liver samples by an HPLC method given in a previous paper (31,32). Briefly, The hydrolysates were evaporated to dryness on a Pierce Reactitherme at 60°C and redissolved in distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Claireaux (1975) summarized much of the earlier work. Other pertinent reports are those of Ambrus, et al (1968), , Frank et al (1977), Frank et al (1978), Mortola (1983), Fisher et al (1991), Langley and Kelly (1994), Kelly and Lubec (1995), Phillips et al (1995), Han, et al (1996), Schock et al (2001), Collard et al (2004), and Higgins et al (2007). One paper stands out from the earlier work on these issues by the authors' clear conclusion that the oxygen was more of a problem than the ventilatory measures used (Nash et al, 1967).…”
Section: Discussionmentioning
confidence: 84%
“…The term oxygen toxicity is in common use (Turrens at al, 1984;Nishiki et al, 1976) but so also are alternative phrases such as hyperoxic injury (Kelly and Lubec, 1995), oxygen-induced lung injury (Ambrus et al, 1968;Phillips et al, 1995), oxidative damage (Collard et al, 2004), and oxidative stress (Schock et al, 2001), inter alia. The important paper by Claireaux (1975) used the neutral phrase, the effect of oxygen on the lung, in the context of what he termed the exudative phase of oxygen toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, high oxygen supplementation coupled with low SOD activity add to oxidative stress, and this may be evidenced by an increase in the by-products of lipid peroxidation (lipid peroxides, malondialdehyde, HNE, alkanes such as ethane and pentane, and isoprostanes) and/or of protein oxidation (carbonyl compounds, o-dityrosine). Newborn infants receiving O 2 supplementation have demonstrably elevated levels of markers of oxidative stress such as exhaled ethane and pentane (Nycyk et al, 1998;Pitkanen et al, 1990), serum HNE (Ogihara et al, 1999), F 2a -isoprostanes in tracheal aspirate or in plasma (Ahola et al, 2004), protein-carbonyl in bronchoalveolar fluid (Gladstone & Levine et al, 1994) or o-dityrosine in urine (Kelly & Lubec, 1995;Lubec et al, 1997). It has been suggested that some of these markers may be higher in the first few days of life in preterm infants who will develop BPD as compared to those who will not (Gladstone & Levine et al, 1994;Hodgman et al, 1969).…”
Section: Superoxide Anionmentioning
confidence: 99%